Serotonin Receptor 1A Variation Is Associated with Anxiety and Agonistic Behavior in Chimpanzees. (23rd April 2019) - Staes, Nicky; Sherwood, Chet C; Freeman, Hani; Brosnan, Sarah F; Schapiro, Steven J; Hopkins, William D; Bradley, Brenda J
Abstract: Serotonin is a neurotransmitter that plays an important role in regulating behavior and personality in humans and other mammals. Polymorphisms in genes coding for the serotonin receptor subtype 1A ( HTR1A ), the serotonin transporter ( SLC6A4 ), and the serotonin degrading enzyme monoamine oxidase A ( MAOA ) are associated with anxiety, impulsivity, and neurotic personality in humans. In primates, previous research has largely focused on SLC6A4 and MAOA, with few studies investigating the role of HTR1A polymorphic variation on behavior. Here, we examined variation in the coding region of HTR1A across apes, and genotyped polymorphic coding variation in a sample of 214 chimpanzees with matched measures of personality and behavior. We found evidence for positive selection at three amino acid substitution sites, one in chimpanzees-bonobos (Thr26Ser), one in humans (Phe33Val), and one in orangutans (Ala274Gly). Investigation of the HTR1A coding region in chimpanzees revealed a polymorphic site, where a C/A single nucleotide polymorphism changes a proline to a glutamine in the amino acid sequence (Pro248Gln). The substitution is located in the third intracellular loop of the receptor, a region important for serotonin signal transduction. The derived variant is the major allele in this population (frequency 0.67), and is associated with a reduction in anxiety, decreased rates of male agonistic behavior, and an increase in socio-positive behavior. These results are the first evidence that the HTR1A gene may be involved in regulating social behavior in chimpanzees and encourage further systematic investigation of polymorphic variation in other primate populations with corresponding data on behavior.